Distinct roles of synaptic and extrasynaptic GABAAreceptors in striatal inhibition dynamics - Luo, Ruixi; Partridge, John G.; Vicini, Stefano (Frontiers in Neural Circuits, 2013)
Striatonigral and striatopallidal projecting medium spiny neurons (MSNs) express dopamine D1 (D1+) and D2 receptors (D2+), respectively. Both classes receive extensive GABAergic input via expression of synaptic, perisynaptic and extrasynaptic GABAA receptors. The activation patterns of different presynaptic GABAergic neurons produce transient and sustained GABAA receptor-mediated conductance that fulfill distinct physiological roles. We performed single and dual whole cell recordings from striatal neurons in mice expressing fluorescent proteins in interneurons and MSNs. We report specific inhibitory dynamics produced by distinct activation patterns of presynaptic GABAergic neurons as source of synaptic, perisynaptic and extrasynaptic inhibition. Synaptic GABAA receptors in MSNs contain the α2, γ2 and a β subunit. In addition, there is evidence for the developmental increase of the α1 subunit that contributes to faster inhibitory postsynaptic current (IPSC). Tonic GABAergic currents in MSNs from adult mice are carried by extrasynaptic receptors containing the α4 and δ subunit, while in younger mice this current is mediated by receptors that contain the α5 subunit. Both forms of tonic currents are differentially expressed in D1+ and D2+ MSNs. This study extends these findings by relating presynaptic activation with pharmacological analysis of inhibitory conductance in mice where the β3 subunit is conditionally removed in fluorescently labeled D2+ MSNs and in mice with global deletion of the δ subunit. Our results show that responses to low doses of gaboxadol (2μM), a GABAA receptor agonist with preference to δ subunit, are abolished in the δ but not the β3 subunit knock out mice. This suggests that the β3 subunit is not a component of the adult extrasynaptic receptor pool, in contrast to what has been shown for tonic current in young mice. Deletion of the β3 subunit from D2+ MSNs however, removed slow spontaneous IPSCs, implicating its role in mediating synaptic input